Urgensi Ijtihad Kolektif dalam Permasalahan Kontemporer - Siti Hanna (Sharia and Law Faculty, 2012)
Islamic exertion (ijtihad) is a tool which makes Islamic law be compatible and relevant to the current progress of time. Some contemporary problems which are being faced by human are needed to be solved from Islamic law perspective. In this regard, to intensify Islamic exertion collectively by involving all scientists from various backgrounds of science and knowledge is a way to solve such kinds of contemporary problems which being faced by mankind generally and Muslim particularly.